2021
DOI: 10.3390/ijms221910869
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin as Ca2+-Dependent Interactor of FTO Dioxygenase

Abstract: FTO is an N6-methyladenosine demethylase removing methyl groups from nucleic acids. Several studies indicate the creation of FTO complexes with other proteins. Here, we looked for regulatory proteins recognizing parts of the FTO dioxygenase region. In the Calmodulin (CaM) Target Database, we found the FTO C-domain potentially binding CaM, and we proved this finding experimentally. The interaction was Ca2+-dependent but independent on FTO phosphorylation. We found that FTO–CaM interaction essentially influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The structural flexibility of CaM is believed to account for its ability to recognize various targets, and the concentration of Ca 2+ is also critical during this process. 75–78 The binding event of CaM with a peptide ligand, Mel, was then explored. The MCE and native MS results of CaM–Mel mixtures (1 : 1) at different Ca 2+ concentrations are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structural flexibility of CaM is believed to account for its ability to recognize various targets, and the concentration of Ca 2+ is also critical during this process. 75–78 The binding event of CaM with a peptide ligand, Mel, was then explored. The MCE and native MS results of CaM–Mel mixtures (1 : 1) at different Ca 2+ concentrations are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of 380 adult Iranian women, the lower levels of HDL were observed in the risk genotypes compared to the non-risk genotype of FTO ( 23 ). The mechanism of FTO polymorphism affecting lipid metabolism has not been fully understood, but it has been reported that FTO could interact with calmodulin-dependent protein kinase II (CaMKII), thereby prolonging CREB phosphorylation and affecting the expression levels of Brain-derived neurotrophic factor (BDNF) and NPY1R neuropeptide Y receptor Y1 (NPY1R), which were related to lipid metabolic process ( 24 ). Besides, FTO catalyzes the demethylation of m6A to alter the processing, maturation, and translation of the mRNAs of lipid-related genes ( 25 ).…”
Section: Discussionmentioning
confidence: 99%